2019
DOI: 10.3390/nu11081809
|View full text |Cite
|
Sign up to set email alerts
|

Weight Matters—Factors Influencing Eating Behaviors of Vulnerable Women

Abstract: Women from low socioeconomic backgrounds are more affected by obesity than men. The influence of weight as a determinant of women’s eating behaviors has seldom been studied, especially in Latin America. In this study, we analyzed the food choices of vulnerable women according to their weight status. We conducted photo-elicitation interviews with 31 women from low-income neighborhoods in Santiago, Chile. Weight and height were measured and participants were divided into normal weight (n = 9), overweight (n = 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 49 publications
0
4
0
1
Order By: Relevance
“…Increasing age was negatively associated with attainment of proper eating behavior in studies carried out in Nepal [ 16 ], Iran [ 41 ], and Canada [ 42 ]. In contrast, Ethiopian [ 20 ], Bahraini [ 43 ] and Spanish [ 44 ] authors demonstrated a positive association of increasing age with healthy eating behavior. Like the findings, the justifications around here are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age was negatively associated with attainment of proper eating behavior in studies carried out in Nepal [ 16 ], Iran [ 41 ], and Canada [ 42 ]. In contrast, Ethiopian [ 20 ], Bahraini [ 43 ] and Spanish [ 44 ] authors demonstrated a positive association of increasing age with healthy eating behavior. Like the findings, the justifications around here are inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the wealthiest social class tends to be influenced more than the disadvantaged ones by these labels. This can lead to situations where women from disadvantaged socio-economic classes seem to be more often affected by obesity than men and other women from middle and upper socio-economic classes, because they often buy from fast food outlets and opt for less fruit and vegetables, reporting making "unhealthy" food choices not because of their own preferences but because of those of the family members for whom they care [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…Se utilizó una encuesta de tendencia de consumo semiestructurada, la cual ha sido utilizada en población chilena con anterioridad 26 . Esta encuesta fue aplicada por el encuestador en formato entrevista.…”
Section: Encuesta De Frecuencia De Consumo Alimentariounclassified